Egg production and mortality of various breeds and crosses of chickens under Sudan conditions - Desai, D.K.; Halbrook, E.R. (1961)
1. White leghorns at the Central Poultry Farm averaged egg production than 50% white Leghorn x Baladi crosses (148 to 132 eggs) under controlled test conditions for a 10 month period in the year 1958/59, but the latter survived slightly better (52% as compared to 65%). 2. White Leghorns lived and laid better than Brown Leghorn and Rhode Island Reds on the Central Poultry farm with egg production over a 10 months period averaging 148, 107 and 108 for each breed respectively, and mortality running, 40%, 75% and 76%. 3. Observation of baladies and various crosses under non-controlled conditions on the Central Poultry Farm showed a tendency for egg production to decrease with increasing White leghorn blood (0%, 87%, 93%) but egg size was increased. All crosses studied laid more and larger eggs than the beladis. Bare neck beladis laid more eggs than other types of baladies.